Iron deficiency in febrile seizures: a prospective case control study - Kumar, Vasanth N.; Hassan, Farogh; Jha, Lata; Kumar, Abnish; Bandopadhyay, Chandreyi; Choudhury, Indranil (International Journal of Contemporary Pediatrics, 2020)
Background: The objective of the study was to evaluate the role of iron deficiency in febrile seizures. Methods: Case control study conducted at Pediatric department of Tertiary care hospital. A total 70 cases and 70 controls were included in the study. Consecutive cases and controls were selected. Cases were children of age group 6 months to 5 years with simple febrile seizures and controls were children of same age group with short febrile illness without any seizures. After consent, detailed history was taken and clinical examination were carried out for both groups. Blood investigations were done to diagnose iron deficiency in both cases and controls. Iron deficiency was diagnosed as per WHO criteria haemoglobin <11 g/dl in cases <5 years mean corpuscular volume<70 fl, mean corpuscular haemoglobin <27 pg and serum ferritin<30 microgram/dl. Results: Mean corpuscular volume was less than 70 fl/ml in 51% cases and 31% controls and mean corpuscular hemoglobin was less than 27 pg/ml in 84% cases and 40% of controls indicating statistically significant association of MCV and MCH between cases and controls .Serum ferritin was less than 30 ng/ml in 44% in cases as compared to 26% of controls, there was statistically significant difference between serum ferritin levels in cases and controls. From the above findings, study showed statistically significant association between iron deficiency anaemia and febrile seizures (p value <0.01; OR- 8.05 (3.6-17.93) (df-1). Conclusions: Iron deficiency is a major risk factor for simple febrile seizures in age group of 6 months to 60 months.